Multilevel Analysis on Factors Affecting Caries Preventive Behavior among Primary School Children: Application of Health Belief Model - Dewi Mustika Ratih; Yulia Lanti Retno Dewi; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Dental caries (tooth decay) is a problem of children’s dental health in the world. Primary school age is a strategic group for the precaution of dental and oral diseases. There is a transition from baby teeth to permanent teeth in the early childhood. Primary school age children do not have good self-care behavior. Therefore, they need parental supervision such as maintenance of dental and oral health. The theory of Health Belief Model (HBM) is used by the community to take positive health action such as precaution of a disease. This study aimed to analyze the caries preventive behavior by using the theory of the Health Belief Model.Subjects and Method: This study used analytic observational method with cross sectional approach. This study was conducted at 25 Primary Schools, Klaten Regency, in September 2019. This study used stratified proportional random sampling and random sampling techniques of 200 primary school children at 25 primary schools in Klaten Regency as the sampling technique. The dependent variable was caries preventive behavior. The independent variables were perceived susceptiblity, perceived severity, perceived benefit, and perceived barrier. This study used questionnaires to collect the data. The data were analyzed by using multilevel analysis on Stata 13.Results: Caries preventive behavior increased with perceived susceptibility (b=0.89; 95%CI=0.85 to 1.69; p=0.030), perceived severity (b=1.59; 95%CI=2.73 to 0.44; p=0.006), perceived benefit (b=1.05; 95%CI=1.97 to 0.12; p=0.026), and perceived barrier (b=-1.54; 95%CI=-2.84 to 0.25; p=0.019). The variation of caries preventive behavior by 7% was determined by variables at the primary school level. This rate was smaller than the standard size of rule of thumb by 8-10%. Therefore, there was a contextual effect shown from the multilevel analysis, but the result was statistically low.Conclusion: There is an effect of perceived susceptibility, perceived severity, perceived benefit, and perceived barrier on caries preventive behavior in primary school children. There is a contextual effect of primary school on caries preventive behavior based on the theory of Health Belief Model, but the result was statistically low.Keywords: multilevel analysis, primary school children, theory of Health Belief Model, precaution of caries.Correspondence: Dewi Mustika Ratih, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: dewiratih1822@gmail.com. Mobile: +625640041822Journal of Health Promotion and Behavior (2019), 4(4): 258-266https://doi.org/10.26911/thejhpb.2019.04.04.02